2021
DOI: 10.1097/brs.0000000000004037
|View full text |Cite
|
Sign up to set email alerts
|

Does Navigation Make Spinal Fusion for Adolescent Idiopathic Scoliosis Safer? Insights From a National Database

Abstract: Study Design. Retrospective Cohort. Objective. To evaluate the effect of computer-assisted navigation (NAV) on rates of complications and reoperations after spinal fusion (SF) for adolescent idiopathic scoliosis (AIS) using a nationally representative claims database. Summary of Background Data. Significant controversy surrounds the reported benefits of NAV in SF for AIS. Previous studies have demonstrated decreased rates of pedicle screw breaches with NAV compared to free-hand methods but no impact on complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In the past few years, modern intraoperative navigation techniques have been increasingly used for more accurate pedicle screw placement. It has been shown that their use results in a decrease in pedicle breach rates while the effect on neurological complication rates remains debated 17 . Regarding our study’s results showing very small distances between the medial pedicle wall and the spinal cord at the curve’s apex, the use of intraoperative navigation needs to be taken into consideration even more as it allows more accurate screw placement.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, modern intraoperative navigation techniques have been increasingly used for more accurate pedicle screw placement. It has been shown that their use results in a decrease in pedicle breach rates while the effect on neurological complication rates remains debated 17 . Regarding our study’s results showing very small distances between the medial pedicle wall and the spinal cord at the curve’s apex, the use of intraoperative navigation needs to be taken into consideration even more as it allows more accurate screw placement.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, our osteotomy techniques are currently performed freehand without any assistance from advanced technology to facilitate bony resections. However, advances in robotics, computer navigation (NAV), and virtual reality (VR) may one day further improve the execution of spinal corrective osteotomies in AIS [ 34 , 35 ]. VR and NAV have been commonly employed to aid in pedicle screw placement, but less has been published about the use of this technology in performing corrective osteotomies.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, there has been a greater focus on navigation-assisted posterior instrumentation [28,29]. However, few studies have focused on the outcome and complication of navigation-assisted one-stage posterior instrumentation in AIS [30]. As a result, the objective of this study was to evaluate outcomes and complications after navigation-assisted one-stage posterior instrumentation for corrective surgery for AIS.…”
Section: Introductionmentioning
confidence: 99%